A High-Quality Haplotype-Resolved Genome of Common Bermudagrass (Cynodon dactylon L.) Provides Insights Into Polyploid Genome Stability and Prostrate Growth - Zhang, Bing; Chen, Si; Liu, Jianxiu; Yan, Yong-Bin; Chen, Jingbo; Li, Dandan; Liu, Jin-Yuan (Frontiers in Plant Science, 2022)
Common bermudagrass (Cynodon dactylon L.) is an important perennial warm-season turfgrass species with great economic value. However, the reference genome is still deficient in C. dactylon, which severely impedes basic studies and breeding studies. In this study, a high-quality haplotype-resolved genome of C. dactylon cultivar Yangjiang was successfully assembled using a combination of multiple sequencing strategies. The assembled genome is approximately 1.01 Gb in size and is comprised of 36 pseudo chromosomes belonging to four haplotypes. In total, 76,879 protein-coding genes and 529,092 repeat sequences were annotated in the assembled genome. Evolution analysis indicated that C. dactylon underwent two rounds of whole-genome duplication events, whereas syntenic and transcriptome analysis revealed that global subgenome dominance was absent among the four haplotypes. Genome-wide gene family analyses further indicated that homologous recombination-regulating genes and tiller-angle-regulating genes all showed an adaptive evolution in C. dactylon, providing insights into genome-scale regulation of polyploid genome stability and prostrate growth. These results not only facilitate a better understanding of the complex genome composition and unique plant architectural characteristics of common bermudagrass, but also offer a valuable resource for comparative genome analyses of turfgrasses and other plant species.